+0

# Converting functions

+1
138
1
+165

How do you get this function: h(x) = −2(x − 2)^2 + 2, to turn into this function: h(x)−2x^2 + 8x − 6?

Absolutezero  Jun 2, 2017

#1
+17613
+1

h(x)  =  -2(x - 2)2 + 2

h(x)  =  -2(x - 2)(x - 2) + 2

h(x)  =  -2(x2 - 2x - 2x + 4) + 2                   [Use FOIL]

h(x)  =  -2(x2 - 4x + 4) + 2                          [Simplify]

h(x)  =  -2x2 + 8x - 8 + 2                             [Distribute the -2]

h(x)  =  -2x2 + 8x - 6                                   [Simplify]

geno3141  Jun 2, 2017
Sort:

#1
+17613
+1

h(x)  =  -2(x - 2)2 + 2

h(x)  =  -2(x - 2)(x - 2) + 2

h(x)  =  -2(x2 - 2x - 2x + 4) + 2                   [Use FOIL]

h(x)  =  -2(x2 - 4x + 4) + 2                          [Simplify]

h(x)  =  -2x2 + 8x - 8 + 2                             [Distribute the -2]

h(x)  =  -2x2 + 8x - 6                                   [Simplify]

geno3141  Jun 2, 2017

### 10 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details